Model Pembelajaran Find Someone Who dan Timed Pair Share untuk Meningkatkan Motivasi dan Hasil Belajar IPS - Firsa Fajar Mahardika; Budi Eko Soetjipto; Siti Malikhah Towaf (Graduate School of Universitas Negeri Malang, 2019)
Abstract: This study aims to describe the application of the Find Someone Who and Timed Pair Share learning models to improve social studies motivation and learning outcomes. The type of research used is Class Action Research. The subject of this study was the VB class of SDN Pakunden 2 with 37 students. The results of this study that the application of the Find Someone Who and Timed Pair Share learning models can increase the motivation and learning outcomes of social studies. At the end of the second cycle, all indicators assessed were able to exceed the specified success criteria.Abstrak: Penelitian ini bertujuan untuk mendeskripsikan penerapan model pembelajaran Find Someone Who dan Timed Pair Share untuk meningkatkan motivasi dan hasil belajar IPS. Jenis penelitian yang digunakan adalah Penelitian Tindakan Kelas. Subjek penelitian ini adalah kelas VB SDN Pakunden 2 dengan jumlah 37 siswa. Hasil dari penelitian ini bahwa penerapan model pembelajaran Find Someone Who dan Timed Pair Share dapat meningkatkan motivasi dan hasil belajar IPS. Pada akhir siklus II, seluruh indikator yang dinilai mampu melampaui kriteria keberhasilan yang ditetapkan.